Influence of the long-term use of oral hygiene products containing stannous ions on the salivary microbiome: a randomized controlled trial - Anderson, Annette C.; Al-Ahmad, Ali; Schlüter, Nadine Kai; Frese, Cornelia; Hellwig, Elmar; Binder, Nadine (Scientific reports, 2020)
Oral hygiene products containing tin are suitable to prevent erosive tooth wear, yet effects on the oral microbiota are not known yet. Therefore, this study determined the salivary microbiome of 16 participants using products with stannous ions for three years (TG) compared with a control group (CG) to assess their influence on the microbiota. Participants were included in a randomized controlled clinical trial (RCT) with biannual visits. Illumina Miseq sequencing revealed as most abundant genera: Streptococcus (TG 14.3%; CG 13.0%), Veillonella (TG 11.3%; CG 10.9%), Prevotella (TG 7.0%; CG 9.8%), Haemophilus (TG 6.6%; CG 7.2%), Porphyromonas (TG 5.9%, CG 5.1%), Leptotrichia (TG 5.8%; CG 4.9%), Actinomyces (TG 4.0%; CG 4.6%) and Neisseria (TG 5.4%; CG 4.2%). Beta-Diversity was not significantly different between groups at both time points, although significant differences between groups were found for certain taxa after three years. The genus Prevotella was found in higher abundance in CG whereas Neisseria and Granulicatella, health-associated taxa, were found more abundantly in TG. Salivary microbiota after three years reflected a composition associated with oral health, hence continual use as a preventive measure for dental erosion can be considered safe and benefitting oral health for patients with a high risk of erosion.
Gesehen am 29.07.2020